A threat to cosmopolitan duties? How COVID-19 has been used as a tool to undermine refugee rights. (1st November 2021) - Barnes, Jamal; Makinda, Samuel M
Abstract : The outbreak of COVID-19 in early 2020 provided cover for some states to take strict and hostile measures against refugees and asylum seekers, thereby privileging self-regarding policies. However, this article shows that the international refugee regime continues to be supported by many states and international actors seeking to emphasise cosmopolitan and 'other'-regarding policies. The article has important implications for study and policy around refugees, and for human rights and security practitioners. Abstract: The outbreak of COVID-19 in early 2020 provided cover for some states to take strict and hostile measures against refugees and asylum seekers, thereby privileging self-regarding over other-regarding or cosmopolitan-oriented policies. The hostile measures, which have included detentions, pushbacks and other refugee deterrence actions not only appeared to shake the refugee system, but they increased the vulnerability of asylum seekers and refugees who continued to be exposed to torture, drownings at sea, trafficking and sexual violence. This development, which included a fine-tuning of some measures that had been hatched before the emergence of COVID-19, appeared to set back efforts to nurture the bonds of global human solidarity and expand moral and ethical boundaries beyond state borders. However, the international refugee regime continues and is supported by many states and other international actors that seek to emphasise cosmopolitan and other-regarding policies. The resilience of the refugee system underlines the fact that international society has a practical and moral basis to challenge exclusionist policies towards asylum seekers and refugees, prevent future harm that might result from asylum deterrence policies and develop more humane forms of international refugee governance.